Natural Grammar - Thornbury S. (Oxford New York Oxford University Press, 2004)
From word to phrase to sentence, this new lexical approach to grammar builds natural idiomatic English. Winner of the 2004 British Council ELT Innovation Award, Natural Grammar shows you how one hundred important English keywords work, the phrases they generate, and the links they make. The emphasis is on natural-sounding language. Plenty of practice is provided in language building. Key Features 100 double-page spreads with explanations and exercises. Reference area with four clear sections: definitions, grammar patterns, collocations, and set phrases. Examples of real language from corpus research. Varied exercises which practise and expand language. Idioms and natural phrases. Language notes on usage.
Keywords: 811.111